Venous thromboembolism in adult elective spinal surgery: a tertiary centre review of 2181 patients. (September 2017) - Fawi, H. M. T.; Saba, K.; Cunningham, A.; Masud, S.; Lewis, M.; Hossain, M.; Chopra, I.; Ahuja, S.
Abstract : Aims: To evaluate the incidence of primary venous thromboembolism (VTE), epidural haematoma, surgical site infection (SSI), and 90-day mortality after elective spinal surgery, and the effect of two protocols for prophylaxis. Patients and Methods: A total of 2181 adults underwent 2366 elective spinal procedures between January 2007 and January 2012. All patients wore anti-embolic stockings, mobilised early and were kept adequately hydrated. In addition, 29% (689) of these were given low molecular weight heparin (LMWH) while in hospital. SSI surveillance was undertaken using the Centers for Disease Control and Prevention criteria. Results: In patients who only received mechanical prophylaxis, the incidence of VTE was 0.59% and that of SSI 2.1%. In patients who were additionally given LMWH, the incidence of VTE was 0% and that of SSI 0.7%. The unadjusted p-value was 0.04 for VTE and 0.01 for SSI. There were no cases of epidural haematoma or 90-day mortality in either group. When adjusted for case-mix, LMWH remained a significant factor (p = 0.006) for VTE, but not for SSI. Conclusion: A peri-operative protocol involving mechanical anti-embolism stockings, adequate hydration, and early post-operative mobilisation is effective in significantly reducing the incidence of VTE. The addition of LMWH is safe in patients at higher risk of developing VTE. Cite this article: Bone Joint J 2017;99-B:1204–9.